The Association Between Thyroid Dysfunction and the Risk of Fractures: A Systematic Review - Alanazi, Mamdouh Mohammed Ramadan; Ali, Alaa Mohamed Saleh Mahdi Sadiq; Alamri, Taif Mohammed; Khan, Adebah; Wali, Razan Ghassan Yousuf; Louhmadi, Hassan Mohammed Abdulaziz; Al Luhaybi, Raneem Abdulaziz; Alotaibi, Abdulmohsen Mubarak S; Alsaeedi, Samaher Nassar Ahmed; Muhammad, Jazza Aamir Fayyaz (Saudi Medical Horizons Journal, 2025)
Thyroid hormones are crucial regulators of bone metabolism. While overt thyroid dysfunction is a recognized risk factor for osteoporosis, the association between subclinical thyroid dysfunction, variations within the euthyroid range, and fracture risk remains complex and less clearly defined. This systematic review aimed to comprehensively evaluate the association between various states of thyroid dysfunction and the risk of incident fractures. A systematic literature search was conducted in accordance with PRISMA guidelines across PubMed, Web of Science, SCOPUS, and ScienceDirect. Studies investigating the association between thyroid dysfunction (overt and subclinical hypo-/hyperthyroidism, euthyroid variations, autoimmune thyroiditis, and thyroid cancer) and fracture risk were included. Two independent reviewers performed study selection, data extraction, and risk of bias assessment using the Newcastle-Ottawa Scale. Thirteen studies met the inclusion criteria. The evidence consistently demonstrated that subclinical hyper-thyroidism and lower thyroid-stimulating hormone (TSH) levels, even within the euthyroid range, were associated with an increased risk of fractures and impaired bone microarchitecture. Several large cohort studies found a lower fracture risk in patients with thyroid cancer, particularly those with postoperative hypoparathyroidism, suggesting a protective effect from intensive calcium and vitamin D supplementation and a low bone turnover state. The relationship between thyroid function and fracture risk is multifaceted. Subclinical hyperthyroidism and low TSH were significant, independent risk factors. The association extends into the euthyroid range, influenced by thyroid hormone sensitivity and autoimmunity. The reduced fracture risk in thyroid cancer patients highlights the critical role of iatrogenic factors and proactive management.